Fundamentals of Entrepreneurship (ENT300) : Snack attack! / Amy Michelle Segi … [et.al.] - Segi, Amy Michelle; Morris, Deborah; Minggan, Jackson Jalie; Sherine, Atopia; Nasheda Alencia, Nyarep (2018)
This business is based on a partnership business where it consists of five members. Our business is a snack shop where we sell finished goods such as snacks and beverages as well as instants food. We are selling a well-known snacks brand from all over Malaysia such as MAMEE, Jack & Jill's and others. The example for beverages is F&N, Season and other.